Neurosarcoidosis Presenting as Aseptic Meningitis in an Immunosuppressed Renal Transplant Recipient. Issue 10 (October 2016) - Held, Elizabeth P.; Iglesia, Edward A.; Johnson, Adam S.; Fang, John Y.; Wilson, Matthew H.; Abel, Ty W.; Lake, Wendell; Siew, Edward D.
Abstract : Background: Sarcoidosis is a presumptive autoimmune disorder characterized by the presence of noncaseating granulomas and is usually treated successfully with immunosuppression. Methods and Results: Here, we describe the case of a 63-year-old male renal transplant recipient with a remote history of pulmonary sarcoidosis on chronic immunosuppression who developed recurrent aseptic meningitis and underwent brain biopsy revealing a diagnosis of neurosarcoidosis. Conclusions: This case highlights the possibility of recurrence of sarcoidosis in the setting of maintenance immunosuppression, the need for heightened awareness of alternative sites of recurrence of autoimmune disease, and future studies to determine the underlying mechanism of recurrence in organ transplant recipients. Abstract : This case report describes an usual case of neurosarcoidosis in a renal transplant patient that was diagnosed late after the patient presented with confusion but eventually was treated successfully.